Investigating the executive functioning and patterns of adherence to antiretroviral therapy among adolescents living with HIV in South Africa - Gama, Lungile Vakele (Faculty of Humanities, 2021)
Given the pathophysiology associated with the Human Immunodeficiency Virus (HIV) and the reported predilection for frontal circuitries and deep white matter, one might expect that executive dysfunction forms part of the neurocognitive profile of people living with HIV. However, such deficits have mainly been reported for adults living with HIV. Adolescence is a period where significant growth and refinement of executive functioning occurs and therefore specific research focused on HIV-positive adolescents is needed. Adolescence is also a developmental period where poor adherence to Antiretroviral Therapy (ART) persists despite marked increases in the national roll out of ART in South Africa, which has significantly decreased HIV-related morbidity and mortality rates. Poor adherence is not only a threat to the efficacy of ART but is also linked to the emergence of drug-resistant HIV strains and identified as a key contributor in the persistence of some cognitive impairments among people living with HIV. Studies show that executive dysfunction can undermine adherence to ART particularly in adolescents, whose frontal lobes are still developing. The first aim of this study was to compare the executive function profile of a group of HIV positive adolescents with that of a matched HIV negative control group. Using P. Anderson's (2002) model, executive functions were considered along the four subdomains: attentional control, processing speed, cognitive flexibility and goal setting. A second aim of the study was to investigate the relationship between executive function and levels of adherence to ART amongst the HIV positive adolescents in the sample. This cross sectional, between-groups study used a comprehensive neuropsychology test battery which was sorted into composite domains to investigate differences in executive functioning between the two study groups of adolescents aged between 14 to 16 (n = 22 in each group) using t-tests. Correlation coefficients were further computed to establish association between adherence and executive functioning. Apart from processing speed (p = 0.42, after the removal of outliers), there were no significant between-group differences in executive functioning outcomes that emerged between the HIV-positive and HIV-negative groups. The neuropsychological test scores for both groups were largely in the borderline range. Correlations between adherence and executive functioning outcomes did not yield any significant associations for each of the executive function domains. The lack of significant between-group differences may be explained by the mitigating effects of ART in the CNS in the HIV-positive group. However, consideration should be given to social factors as these may be important mediators of cognition and may therefore confound neuropsychological performance outcomes for both groups. Although the findings in the current study did not conclusively provide evidence for the role of executive functions in adherence, given the noted limitations, further studies with larger samples should confirm such outcomes.